(untitled) - Carrier, Jim (Camden, Me., 2001)
In October 1998, one of the most savage storms in Atlantic history cornered a 282-foot passenger sailing ship against an exposed Caribbean coastline. With nowhere to hide and no time to run, Fantome turned to face Hurricane Mitch;s assault of 180 mile-per-hour winds and 50-foot seas. As the eye of the storm approached, Fantome;s satellite phone went dead. The ship and its 31 crewmembers simply disappeared, leaving only questions that won;t go away. The Ship and the Storm explores every facet of this tragic story. Was the ship seaworthy? Why did the captain put to sea with the storm approaching? What happened in the eye wall of the worst hurricane in 200 years? This riveting real-life drama is forensic journalism at its finest, taking us from the deck of the ship, to cruise company headquarters in Miami, to the National Hurricane Center. From Jim Carrier;s extensive on-site research and hundreds of hours of interviews emerges a story of hubris, courage, and the power of nature.
Keywords: Shipwrecks,Nạn đắm tàu; Caribbean Sea,Vùng biển Caribê